2016
DOI: 10.12968/ijtr.2016.23.5.207
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the experience of early supported discharge from the perspective of stroke survivors

Abstract: Aims: To explore the experience of early supported discharge from the perspective of stroke survivors in Ireland. Methods: A qualitative research design was used. Participants (n=4) were purposively selected, and each had undergone early supported discharge. Semi-structured interviews were carried out with each of these individuals, and were then analysed using interpretative phenomenological analysis. Results: Two superordinate themes emerged from the analysis: (1) Getting out and getting on. (2) Understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The 14 studies in this review reported on the experiences of 390 participants in total. The study with the smallest number of participants was Collins and colleagues (n = 4) [ 51 ] while the study with the largest number of participants was Fisher and colleagues (n = 147) [ 40 ]. The age range of participants with stroke ranged from 32 years [ 40 ] to 92 years [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 14 studies in this review reported on the experiences of 390 participants in total. The study with the smallest number of participants was Collins and colleagues (n = 4) [ 51 ] while the study with the largest number of participants was Fisher and colleagues (n = 147) [ 40 ]. The age range of participants with stroke ranged from 32 years [ 40 ] to 92 years [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The aim of five included studies aligned very closely with the focus of this synthesis. These five studies explored the experience of ESD from the perspective of the person after stroke and/or carers [ 40 , 42 , 44 , 51 , 54 ]. Fisher and colleagues [ 40 ] report articulated a more focused aim for exploring HCPs perspectives, namely, to understand the interaction between contextual influences, core intervention components and the reasoning and actions of ESD team members.…”
Section: Resultsmentioning
confidence: 99%
“…The papers were published between 2000 and 2017, with two studies conducted in Australia, 46,47 six in Sweden [48][49][50][51][52][53] and the rest in the UK. 13,19,23,38,39,[54][55][56][57][58][59][60] Ten studies focused on stroke ESD services, 13,19,23,38,46,47,49,50,54,58 four investigated community stroke rehabilitation services 39,57,59,60 and six examined stroke patients' transition from hospital to home. 48,[51][52][53]55,56 Data collection methods mainly involved qualitative interviews; two studies conducted surveys, 46,56 two undertook observations, 19,59 two used consensus methods and one provided insights from a service development project.…”
Section: Resultsmentioning
confidence: 99%
“…Interviews with patients and carers highlighted the importance of having access to stroke-specialist information in appropriate formats. 38,49,55,58 Managing endings through timely and constant communication was identified as one of the factors contributing to a positive patient experience in a study by Cowles et al 54…”
Section: Communication With Patients and Carersmentioning
confidence: 99%
“…A number of primary qualitative research studies have also explored experiences and views of ESD from the perspective of persons with stroke, their family members, caregivers and healthcare professionals ( Chouliara et al , 2014 ; Collins et al , 2016 ; Lou et al , 2017 ). It is imperative to synthesise findings pertaining to the experiences and perspectives of persons with stroke, family members, caregivers and healthcare professionals of ESD in order to inform practice as well as policy development.…”
Section: Introductionmentioning
confidence: 99%